The faithful spy : a novel - Berenson, Alex. (New York : Jove Books, 2008)
John Wells, an undercover operative who has infiltrated al Qaeda, is trapped between his terrorist associates and the CIA, which no longer trusts his loyalty, when he becomes a prime suspect in two bombings in Los Angeles.
Originally published: New York : Random House, 2006.
Keywords: Qaida (Organization) -- Fiction; Terrorism -- Fiction; Intelligence service -- Fiction; Suspense fiction; Spy stories